KONSTRUK EMOSI MARAH PERSPEKTIF AL-QUR’AN - Miftah Ulya (UIN Mataram, 2020)
Emotional anger is an urgent and has an essential role in living human life, besides he is also praiseworthy as well as the nature and attitude to watch out for, because anger is also the most active role in things that are self-preservation, family, and other social communities. Anger emotions arise as a result of feelings of displeasure with people other than themselves, or certain objects that are closely related to the personality and inner experience experienced by someone. In the Qur'an the expression